Beyond the DSGE straitjacket - Mohammad Hashem Pesaran; Ron P. Smith (Center for Economic Studies and ifo Institute (CESifo), 2011)
Academic macroeconomics and the research department of central banks have come to be dominated by Dynamic, Stochastic, General Equilibrium (DSGE) models based on microfoundations of optimising representative agents with rational expectations. We argue that the dominance of this particular sort of DSGE and the resistance of some in the profession to alternatives has become a straitjacket that restricts empirical and theoretical experimentation and inhibits innovation and that the profession should embrace a more flexible approach to macroeconometric modelling. We describe one possible approach.
Keywords: I20; D72; 330; macroeconometric models; DSGE; VARs; long run theory; Ökonometrisches Makromodell; Dynamisches Gleichgewicht; Kritik; Theorie